Penerapan E – Government Melalui Arsip Digital Desa: Studi Kasus Desa Larangan Kecamatan Candi Kabupaten Larangan - Andini, Flosovi; Mursyidah, Lailul (Universitas Muhammadiyah Sorong, 2024)
The aim of this study is to examine and evaluate the phases, procedures, and challenges associated with the implementation of e-government through digital archives in the village's neighborhood unit (RT) 47 in Larangan Village. Employing a qualitative methodology with a descriptive research design, the findings indicate that the e-government implementation process via the village digital archives is currently in the preparatory phase. Second, the procedure for implementing e-government through the village digital archives in Larangan Village involves recording all residents’ information, such as Head of Family, Address, Telephone, House Status, Number of family members, as well as Family Card number and National Identification Number (NIK), which are replaced with house numbers to ensure data security. This data is then inputted by the person in charge into the neighborhood unit (RT) 47 residents’ database application. The obstacles in implementing e-government through the village digital archives include human resources as successors of the application operator, application interoperability with the government, and the absence of village regulations to mandate digitization in each RT.